Independence of Judges In Imposting Community Service Criminals In Child Criminal Cases - Sartika, Sarai Dwi (Scholar Center, 2023)
Children are the next generation of the nation, where a child who is involved in a crime must still be protected by the state. The imposition of a community service crime is an alternative type of punishment to a crime of deprivation of liberty or imprisonment which has the aim of preventing children from the negative effects of applying prison sentences. After the birth of Government Regulation Number 58 of 2022 concerning Forms and Procedures for Implementation of Crime and Actions Against Children, there are several obstacles such as the inconsistency of these regulations with the The Juvenile Justice System Law and the Judicial Powers Law, which gives rise to the independence of judges in deciding juvenile criminal cases, besides this it is still the limited resources of competent judges and the lack of infrastructure are obstacles to imposing community service crimes for child cases. The thesis will discuss what are the obstacles in making community service decisions and how to overcome these obstacles. This research method uses normative juridical research methods, which use a qualitative approach. Furthermore, it is known that there is a need for normalization of the implementing regulations for the Juvenile Justice System Law, training for Judge Resources through certification, and the importance of The Ministry of Law and Human Rights having an MOU with government and private institutions for the certainty of community service criminal places for judges in deciding cases.